Design and Implementation of IOT Connection With Websocket Using PHP - Friendly; Ajulio Padly Sembiring; Sharfina Faza; Andam Lukcyhasnita (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
IOT design and connecting between devices has been developed in recent years. Connection between device has been done from using Bluetooth, internet thru api, restfull api, socket, websocket, mttq and many others method. Api and socket is the most used method in connecting IOT devices. This reasearch tends to implement the websocket in connecting and controlling IOT devices. From the application of this research, the devices can be connected and implement with high speed of average 700ms with loaded netword. According to the results of the test, number of loads and data size can increase the time duration for each communication between IOT devices and websocket server. The larger the data, the more possible the anomaly may accured where the number of connections will experience lagging in command execution between the IOT devices and the controller The bidirectional connection in websocket make the data exchange posibbly fast.